Heartbeats and high scores: esports triggers cardiovascular and autonomic stress response - Ketelhut, Sascha; Nigg, Claudio R. (Frontiers in Sports and Active Living, 2024)
Introduction Gaming is often labeled as sedentary behavior. However, competitive gaming, also known as esports, involves significant cognitive demands and may induce stress. This study aims to investigate whether the psychophysical demands during esports elicit a physiological stress response. Methods Fourteen FIFA 21 and thirteen League of Legends players (23.3 ± 2.8 years) were recruited for the study. Heart rate (HR), root mean square of successive differences between normal heartbeats (RMSSD), peripheral and central blood pressure (BP), pulse wave velocity (PWV), and energy expenditure (EE) were assessed during supine rest, seated rest, and competitive FIFA or League of Legends matches. Results No significant group × condition interactions were observed for any of the outcomes. However, there were significant increases in mean HR (p < 0.001, ηp2 = 0.383), RMSSD (p = 0.019, ηp2 = 0.226), peripheral systolic BP (p < 0.001, ηp2 = 0.588), peripheral diastolic BP (p = 0.005, ηp2 = 0.272), central systolic BP (p = 0.005; ηp2 = 0.369), central diastolic BP (p = 0.016, ηp2 = 0.313), PWV (p = 0.004, ηp2 = 0.333), and EE (p < 0.001, ηp2 = 0.721) during both games compared to the seated rest condition. Conclusion Despite the sedentary nature of esports, the psychophysical demands appear to elicit physiological responses. Interestingly, no significant differences were found between the different game genres.